Penerapan Metode Fast Independent Component Analysis (FastICA) dalam Memisahkan Vokal dan Instrumen Seni Geguntangan - Luh Arida Ayu Rahning Putri; I Gede Erwin Winata Pratama; I Dewa Made Bayu Atmaja Darmawan; A. A. I. N. Eka Karyawati; Ida Bagus Made Mahendra; I Ketut Gede Suhartana (Jurnal Buana Informatika, 2022)
Abstract. Application of Fast Independent Component Analysis (Fastica) Method in Separating Vocals and Instruments in Geguntangan. Gamelan Geguntangan is often used in religious ceremonies to accompany ceremonies and entertain the public. Along with its development, the Geguntangan gamelan is also used to accompany the Pesantian. Geguntangan recording plays instruments and vocal sounds, most of which have been mixed. The mixed sounds caused the learning process to be less effective for people who will study Pesantian. The students could not focus because of the distracting sound of the instrument. This study aims to separate the sound of instruments and vocals of Geguntangan using deflationary-based FastICA. The non-linear function used is Logcosh. This study also examines the effect of mixing matrix variables and alpha values on nonlinear functions on SDR, SIR, and SAR values. The results of the paired t-test carried out by these two values did not have a significant effect on SDR, SIR, and SAR. The difference in the average time of the mixing matrix testing process is 0.09 seconds and 0.42 seconds for testing the alpha value.Keywords: Pesantian, Geguntangan, BSS, FastICA, Deflationary Based. Abstrak. Gamelan Geguntangan sering dipakai dalam upacara keagamaan baik untuk mengiringi jalannya upacara dan hiburan masyarakat. Seiring perkembangannya, gamelan Geguntangan juga digunakan untuk mengiringi Pesantian. Pada rekaman Geguntangan terdapat suara instrumen dan vokal yang sebagian besarnya sudah tercampur. Hal ini menyebabkan proses belajar yang kurang efektif bagi orang yang akan belajar Pesantian. Para pemelajar tidak bisa fokus karena adanya suara instrumen yang mengganggu. Penelitian ini bertujuan untuk memisahkan suara instrumen dan vokal seni Geguntangan menggunakan deflationary based FastICA. Fungsi non linear yang digunakan adalah Logcosh. Penelitian ini juga menguji pengaruh variabel matriks pencampuran dan nilai alpha pada fungsi nonlinear terhadap nilai SDR, SIR dan SAR. Hasil uji-t berpasangan yang dilakukan kedua nilai ini tidak mempunyai pengaruh yang signifikan terhadap SDR, SIR dan SAR. Selisih rata-rata waktu proses pengujian matriks pencampuran ialah 0.09 detik dan 0.42 detik untuk pengujian nilai alpha.Kata Kunci: Pesantian, Geguntangan, BSS, FastICA, Deflationary Based.